Introducing geology : a guide to the world of rocks - Park, Graham (Dunedin Academic Press Ltd, 2019)
Our world is made of rock. Those who live in a landscape where rock outcrops are obvious will have wondered about the kind of rock they are looking at and how they came to be where they are now. Graham Park explains in simple terms what geology can tell us about the world.